Pengaruh Pelayanan Berbasis Teknologi Informasi Listrik Prabayar dan Kerelasian Pelanggan terhadap Kepercayaan Pelanggan dan Dampaknya pada Citra Perusahaan - Fajar Suroyo (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2015)
Prepaid Electricity information technology services (LPB) and Customers Relations who have been and services are being implemented by PLN examined in this study does add to the sense of customers’ trust that can influencing in increasing the company’s image. The study used a survey of 250 customers of prepaid electricity in the province of West Kalimantan. The results using descriptive analysis approach showed that customers information technology services and customer relations, customer trust and corporate image according to the customer is already good. While the approach of verification analysis found that the use of information technology is growing rapidly in support of customer service will greatly help increase customers’ trust in the company’s products, which leads to improved corporate image.